CD3+CD4−CD8− T cells: a new potential therapeutic target in treating autoimmune diseases - Li, Xin; Guo, Di; Zou, Isabelle Xinyue; Zhao, Lingyan; Yang, Na; Liu, Yang (Frontiers in Immunology, 2025)
As a key lymphocyte population in shaping and controlling adaptive immune response, T cells play an important immunomodulatory role in the early stages of autoimmune diseases. Although CD3+CD4−CD8− T (DNT) cells constitute only a small proportion of peripheral T lymphocytes, they may be closely linked to the occurrence and development of autoimmune diseases. However, the role of DNT cells in autoimmune disease pathogenesis still needs to be elucidated. In this review, we first present the origin, functions, and heterogeneity of DNT cells. We then summarize the role of DNT cells in the pathogenesis of various autoimmune diseases. Subsequently, we clarify the recent advances in the applications of DNT cell-based therapy for autoimmune diseases and outline potential drugs (including active ingredients extracted from Chinese medicinal treatments) and approaches that can target the proliferation and expansion of DNT cells. Lastly, the limitations and challenges of applying DNT-cell-based therapy are analyzed. In conclusion, we present an overview to further the understanding of the role of DNT cells in autoimmune disease pathogenesis and of DNT cells as a potential therapeutic tool for immune disorders.